PENERAPAN METODE SOLFEGIO PADA PEMBELAJARAN VOKAL PADUAN SUARA GEREJA - Novi Yanti Gea; Yunatan Krisno Utomo; Feritrio Harmony (JOURNAL of THEOLOGICAL STUDENTS, 2022)
The purpose of this study is to find out how the process of vocal learning with the Solfegio method is and what are the impacts of its application.This research was conducted by research and development (R&D) methods and data triangulation. Where the researcher collects several sources of data that will be processed into the final result of this research. The data techniques analysis is done by reducing the data, presenting the data and concluding. The theoretical basis discusses the meaning of solfegio, and the learning methods of ear training, sight reading, and sight singing.The results of this study are the vocal learning process with the Solfegio method and the impacts of the application Solfegio method has been successfully applied. The solfegio method helps choir members learn both number and block notation in scores. The conclusion of this study shows that the application of the solfegio method is the right strategy for learning choir vocals to make it easier to understand the songs being taught. The existence of this choir is not only a place to channel singing talent, but also to serve the Lord Jesus with heavenly songs.Â Â